Excess cases of influenza and the coronavirus epidemic in Catalonia: a time-series analysis of primary-care electronic medical records covering over 6 million people - Coma Redon, E; Mora, N; Prats-Uribe, A; Fina Avilés, F; Prieto-Alhambra, D; Medina, M (BMJ Publishing Group, 2020)
Objectives There is uncertainty about when the first cases of COVID-19 appeared in Spain. We aimed to determine whether influenza diagnoses masked early COVID-19 cases and estimate numbers of undetected COVID-19 cases.